Privatization and Financial Market Development: Theoretical Issues - Gabriella Chiesa; Giovanna Nicodano (Fondazione Eni Enrico Mattei (FEEM), 2003)
Stock market capitalization in developed countries grew while massive privatization plans were in progress. It is however possible that stock market development would have occurred anyway. Below we identify features that are specific to share-issue privatizations (SIPs) and should a priori impact on market liquidity and market size. A positive correlation between such features and market development in a cross section of countries would support the claim that certain types of SIPs contribute to stock market development.
Keywords: L33; G14; 330; Privatization; Financial market development; Privatisierung; Börsengang; Finanzmarkt; Liquidität; Theorie